Food spectrum and feeding intensity of Accrossocheilus hexagonolepis (McClelland), an enedemic rheophilic teleost of commercial importance of Assam Himalayas - ., Balendra; Das, K R; Goswami, Umesh C (Indian Journal of Fisheries, 2011)
The food of Accrossocheilus hexagonolepis (McClelland) consists mainly of algae, unidentified vegetable matter, protozoan species, rotifers, nematodes, insects, crustaceans, unidentified animal matter, sand and detritus. Algae is the principal (20-43 %) food item (Bacillariophyceae, Chlorophyceae, Cyanophyceae, Euglenophyceae and Rhodophyceae). The gastrosomatic and stomach fullness indices of the species showed a high feeding intensity in either prespawning or post spawning period